Current Overview of Neonatal Convulsions - Acar, Duygu Besnili (Sisli Etfal Hastan Tip Bul, 2019)
Neonatal convulsions are one of the most common emergency neurological events in the early period after birth. The frequency has been reported to be 1.5 to 3 in 1000 live births. It has been established that the convulsion threshold is lower in infants due to immature neonatal neurons and differences in neurotransmitters. Hypoxic ischemic encephalopathy is the most common etiology in neonatal convulsions. Other causes vary, and may be related to the level of development of the country. Convulsions are classified into 4 different types according to the clinical findings. The most common is the subtle (undefined) type of seizure; the other types are defined as clonic, tonic, and myoclonic seizures. Non-epileptic paroxysmal movements frequently seen in the neonatal period, should not be confused with seizures. The most common non-epileptic paroxysmal movements are jitteriness, benign neonatal sleep myoclonus, and hyperekplexia. A newborn that experiences convulsions should be hospitalized and monitored with continuous video electroencephalogram, if possible. If an initial rapid evaluation detects an acute metabolic disorder, treatment is provided, and, if warranted, it will be followed by a plan for further treatment with anticonvulsant drugs. Phenobarbital is still currently recommended as first-line therapy, though there are studies of other anticonvulsant drugs. Levetiracetam and phenytoin are commonly used as second-step anticonvulsant drugs. The aim of treatment should be not only to stop acute symptomatic seizures, but also to reduce the risk of brain damage and to minimize the possible negative effects of epilepsy and neurological deficits.